Screening for hepatic fibrosis and steatosis in Turkish patients with type 2 diabetes mellitus: A transient elastography study - DEMİR, MERYEM; YILMAZ, YUSUF (AVES, 2019)
Background/Aims: Non-alcoholic fatty liver disease is highly prevalent in patients with type 2 diabetes mellitus (T2DM). The aim of the present study was to investigate the potential usefulness of transient elastography (TE), which is a technique that allows measuring both fibrosis and liver fat content simultaneously, as a screening tool for hepatic involvement in Turkish patients with T2DM. Materials and Methods: We obtained liver stiffness measurements (LSMs, as a measure of fibrosis) and controlled attenuation parameter (CAP, as a marker of steatosis) in 124 (46 males and 78 females; mean body mass index (BMI): 33.2 +/- 6.6 kg/m(2)) Turkish patients with T2DM. The prevalence rates of overweight, obesity, and metabolic syndrome in our sample were 28.2%, 64.5%, and 77.4%, respectively. Probe-specific LSM cut-off values were used to define advanced fibrosis (>= F3) and cirrhosis (F4) (M probe: F3=9.6-11.4 kPa, F4 >= 11.5 kPa and XL probe: F3=9.3-10.9 kPa, F4 >= 11.0 kPa). Mild, moderate, and severe steatosis were defined as CAP 222-232 dB/m, CAP 233-289 dB/m, and CAP >= 290 dB/m, respectively. Results: Advanced fibrosis and cirrhosis were identified in 21 (16.9%) and 10 (8.0%) patients, respectively. TE-defined hepatic steatosis (CAP>222 dB/m) was detected in 117 (94.3%) patients. Mild, moderate, and severe steatosis were identified in 0, 29, and 88 patients, respectively. Conclusion: TE is a useful non-invasive imaging modality to screen for liver involvement in Turkish patients with T2DM. High rates of TE-defined fibrosis and steatosis in our sample reflect the presence of an elevated mean BMI.
Keywords: Type 2 diabetes mellitus; non-alcoholic fatty liver disease; fibroscan; prevalence; obesity; metabolic syndrome; FATTY LIVER-DISEASE; CONTROLLED ATTENUATION PARAMETER; ASSOCIATION; PREVALENCE; ULTRASOUND; DIAGNOSIS